Learners’ attitudes toward using wikis and forums for collaboration on case problems - Ioannou, Andri; Artino, Anthony R.; Brown, Scott W. (My University, 2015)
In a case study using quasi-experimental methods (within-subject repeated measures with counterbalancing), differences in students’ attitudes were assessed when they used a wiki with discussion (i.e., an enhanced wiki) and a forum with attached MS Word documents for virtual collaboration on case problems. Data from 63 online learners working with both tools was collected. Statistically significant differences were found on a technology experience measure, in favor of the wiki tool. Further, qualitative data supported this finding. This study is an extension of the authors’ previous work, adding to a holistic picture of collaborative learning using wikis and forums in online learning settings.
Keywords: Attitudes; Wiki; Collaborative learning; Forum; MediaWiki; Online learning; Technology experience; Threaded discussion